The Safety and Tolerability of Lumbrokinase DLBS1033 in Healthy Adult Subjects - Tjandrawinata, R. R.; Yunaidi, D. A.; Susanto, L. W. (Drug Research, 2016)
Background: This study was aimed to evaluate the safety and tolerability of Lumbrokinase DLBS1033 in healthy adult subjects.Methods: This was a 2-arm, randomized, double-blind, placebo-controlled, cross-over study over 14 days of treatment with DLBS1033 490 mg 3 times daily. Eligible subjects were enrolled at Period 1 and allocated to receive either test drug or placebo, and underwent a clinical assessment including vital signs, electrocardiography, laboratory examination (hemostasis parameters, routine hematology, liver and renal function), the presence of hemorrhagic symptoms and allergic reactions. Afterwards, they went on to a 2-week washout period, and then were crossed-over to receive the alternate drug at Period 2. The procedure of Period 1 was repeated in the same manner with the alternate drug at Period 2.Results: Of 20 subjects enrolled, one subject was lost to follow-up on Evaluation Day-14 of Period 2. Bleeding risk was relatively low as demonstrated by insignificant differences in hemostasis parameters between DLBS1033 and Placebo. Neither were there significant differences between DLBS1033 and Placebo in terms of hematological parameter, each blood chemistry parameter (liver function, renal function, lipid profile, fasting blood glucose), abnormality proportions of urine test, stool occult blood, and ECG interpretation. There were no hemorrhagic symptoms (petechiae, epistaxis, hematoma) and allergic reactions encountered by study subjects during the treatment with DLBS1033 and Placebo.Major Conclusion: DLBS1033 given at the dose of 490 mg 3 times daily was safe and tolerable in healthy adults.
Keywords: DLBS1033; Lumbricus rubellus; lumbrokinase; safety